PEMBELAJARAN SEJARAH DI SMA NEGERI 2 LEMBANG JAYA KABUPATEN SOLOK - PUTRA, ENDI; NURHUDA, AHMAD; Meldawati, Meldawati (Pendidikan Sejarah, 2013)
ABSTRACTÂ Efforts to improve the quality of teaching history in high school constantly made, both conventional and innovative. Efforts to improve the success of learning History in the Classroom is the role of the teacher in the classroom to manage well during the learning process takes place. The purpose of this study is to to know about planning, implementation and evaluation of the teaching of history in SMA Negeri 2 Lembang Jaya Kabupaten Solok. This research uses a qualitative approach with descriptive research. The study was conducted in the Class XI students of SMA Negeri 2 Lembang Jaya. The main instrument in this study was the researcher, as executor, observers, and at the same time as data collectors. Collecting data in this study conducted by Field Research (research field) consisting of observations (observation), Interview (interview), as well as documentation. The analysis in this study is a non-statistical analysis according to the descriptive data. The results showed in the planning stages teachers need to prepare students needs analysis , materials , create a syllabus , preparing lesson plans , preparing the instruments learning , choosing instructional strategies that will be implemented in the classroom and providing learning resources and teaching materials for learners . In the process of implementation of the teacher conducting an analysis of the needs and problems experienced by students individually as not having its own handbook ; lack of concentration students to lessons ; students are less active ; attract the attention of others.